Analisis Kualitatif tentang Dampak Sosial dan Ekonomi Pembangunan Pembangkit Listrik Tenaga Air dalam Perspektif Konseling Masyarakat - Syafika, Muhammad Akbar Yuda; Firmasyah, Firmasyah; Saputra, Wisnu; Juita, Nellya (UIN Kiai Haji Achmad Siddiq Jember, 2025)
This study analyzes the social in Perspectif of civils and economic impacts of hydroelectric power plant (PLTA) development using a qualitative approach. The research scope includes social, economic, and environmental changes experienced by local communities. The data collection techniques in this study were in-depth interviews, field observations, and document analysis. The results indicate that although hydropower development offers economic advantages like employment opportunities and infrastructure enhancements, it also causes social impacts, including displacement, livelihood changes, and land ownership conflicts. Additionally, changes in water ecosystems affect local agriculture and fisheries.This study concludes that sustainable planning and community involvement are crucial in decision-making processes. By integrating social and economic considerations, hydroelectric projects can achieve long-term benefits that are more equitable for all stakeholders